The Influence of Viral Marketing and Endorsers on Brand Awareness and Purchasing Decisions for Street Boba Pekanbaru Products - Rahmadani, Novi; Wijayanto, Gatot; Wasnury, Rendra (CV. Rayyan Dwi Bharata, 2024)
This study aims to determine and analyze the influence of Viral Marketing and endorsements on purchasing decisions with Brand Awareness as an moderatingvariable on Street Boba Pekanbaru. The approach used in this research is quantitative using the SEM-PLS model and SmartPls 4.0 software as tools for this research. Data ware obtained through distributing questionnaires to 385 respondents. The results of this research reveal that: (1) there is a positive and significant influence of Viral Marketing on purchasing decisions at Street Boba Pekanbaru, (2) there is a positive and significant influence of Endorser s on purchasing decisions at Street Boba Pekanbaru, (3) there is a positive and significant influence of Viral Marketing on Brand Awareness on Street Boba Pekanbaru, (4) there is a positive and significant influence of Endorser s on Brand Awareness on Street Boba Pekanbaru, (5) there is a positive and significant influence of Brand Awareness on purchasing decisions on Street Boba Pekanbaru. (6) there is a positive and significant influence of Viral Marketing on purchasing decisions with Brand Awareness as an moderatingvariable on Street Boba Pekanbaru, (7) there is a positive and significant influence of Endorser s on purchasing decisions with Brand Awareness as an moderatingvariable on Street Boba Pekanbaru.